Gas-phase ion/ion reactions of peptides and proteins: acid/base, redox, and covalent chemistries - Prentice, Boone M. (2012)
Gas-phase ion/ion reactions are emerging as useful and flexible means for the manipulation and characterization of peptide and protein biopolymers. Acid/base-like chemical reactions (i.e., proton transfer reactions) and reduction/oxidation (redox) reactions (i.e., electron transfer reactions) represent relatively mature classes of gas-phase chemical reactions. Even so, especially in regards to redox chemistry, the widespread utility of these two types of chemistries is undergoing rapid growth and development. Additionally, a relatively new class of gas-phase ion/ion transformations is emerging which involves the selective formation of functional-group-specific covalent bonds. This feature details our current work and perspective on the developments and current capabilities of these three areas of ion/ion chemistry with an eye towards possible future directions of the field.